Problem-Based Learning Model for Improving Problem-Solving Skills and Critical Thinking of Elementary School Students - Meisya, Rovika; Jannah, Raudhatul; Aqida, Debby Silvia; Khairunnisa, Destia (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2023)
The teaching of science emphasizes that students should learn independently so that they can enhance their scientific attitude, thinking, working, and communication skills as life skills aspects. One of the fundamental problems found in education today is the low absorption capacity and critical thinking of students. One instructional model that can be used in science education is Problem-Based Learning (PBL). This research is conducted using a literature review method by analyzing previous studies on the improvement of learning outcomes and the critical thinking abilities of students through problem-based learning. The data sources for this research come from various previous research literature that has analyzed the use of problem-based learning models to enhance learning outcomes and the critical thinking abilities of students. Problem-based learning is intended, among other things, to help students develop thinking skills and problem-solving skills.